1995
DOI: 10.1152/ajplung.1995.268.5.l729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain-enhanced fetal lung cell proliferation is mediated by phospholipase C and D and protein kinase C

Abstract: The signaling pathways by which intermittent strain (60 cycles/min, 15 min/h) regulates proliferation of mixed fetal rat lung cell in vitro have been investigated. Adenosine 3',5'-cyclic monophosphate (cAMP) content and cAMP-dependent protein kinase (PKA) activity were not affected by strain. The stimulatory effect of strain on DNA synthesis was also not influenced by the cyclic nucleotide-dependent protein kinase inhibitors H-8 or HA-1004, the adenylate cyclase inhibitor SQ-22536, or a PKA inhibitor and cAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…Phosphorylation of PLCγ1-Tyr 783 plays an important role in the signal transduction of cell proliferation and migration by mediating the downstream signaling proteins, including ERK1/2 (16,22). Husain et al (35) confirmed that activation of PLCγ1 is required for vascular endothelial growth factor receptor-2 (VEGFR-2)-induced endothelial cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation of PLCγ1-Tyr 783 plays an important role in the signal transduction of cell proliferation and migration by mediating the downstream signaling proteins, including ERK1/2 (16,22). Husain et al (35) confirmed that activation of PLCγ1 is required for vascular endothelial growth factor receptor-2 (VEGFR-2)-induced endothelial cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…PLCγ1, as one of the serine threonine kinases of PLC, plays an important role in the signal transduction for the regulation of the cellular mitogenic effects in various types of cells in response to different stimuli, including cyclic mechanical stimulation (19)(20)(21)(22). Liu et al (22) have demonstrated that intermittent mechanical strain enhances the cellular proliferation and phosphorylation of PLCγ1 in fetal lung cells, and the mitogenic response to cyclic mechanical stimulation is mediated by activated PLCγ1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the role played by PLC in the peptide-induced PLD activation and superoxide anion formation, we used U-73122, a PI-specific PLC inhibitor [21]. As shown in Figure 5A, preincubation of the cells with U-73122 before the stimulus totally inhibited the peptide-induced intracellular calcium mobilization caused by PI hydrolysis.…”
Section: Wkymvm Induces Pld Activation In Human Monocytesmentioning
confidence: 99%
“…Concurrent with these physiological studies, research over the past decade has shown that mechanotransduction (i.e., the conversion of a mechanical stimulus such as cell deformation into biochemical and molecular alterations) plays a crucial role in determining the structure and function of a number of tissues, including the lung (12)(13)(14). Studies in vitro and in vivo have found that both the degree and the pattern of mechanical stretch are important in determining cell responses (14,15).…”
Section: Introductionmentioning
confidence: 99%